2009
DOI: 10.1007/s10532-009-9310-y
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate bioavailability in soil

Abstract: Biodegradation of glyphosate in sod-podzol soil by both the indigenous micro flora and the introduced strain Ochrobactrum anthropi GPK 3 was studied with respect to its sorption and mobility. The experiments were carried out in columns simulating the vertical soil profile. Soil samples studied were taken from soil horizons 0-10, 10-20, and 20-30 cm deep. It was found out that the most of the herbicide (up to 84%) was adsorbed by soil during the first 24 h; the rest (16%) remained in the soluble fraction. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 22 publications
(34 reference statements)
1
21
0
1
Order By: Relevance
“…Bergstrom et al (2011) reported that the residues of glyphosate and AMPA were mainly detected in topsoil (0-30 cm), despite the application of glyphosate 748 d earlier, and Shushkova et al (2010) reported that 57% of the glyphosate was concentrated in the 0-10 cm soil layer after 7 d. Studies also showed that glyphosate is initially absorbed mostly in the upper 2 cm of soil rather than transported and absorbed after a few days in deeper soil horizons (Rampazzo et al, 2013) which is similar to Yang et al (2015) and our results (Tables 2 and 3). Glyphosate and AMPA content then correspondingly decreased significantly in deeper soil layers (2-10 cm) and were even below the limit of detection in some layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergstrom et al (2011) reported that the residues of glyphosate and AMPA were mainly detected in topsoil (0-30 cm), despite the application of glyphosate 748 d earlier, and Shushkova et al (2010) reported that 57% of the glyphosate was concentrated in the 0-10 cm soil layer after 7 d. Studies also showed that glyphosate is initially absorbed mostly in the upper 2 cm of soil rather than transported and absorbed after a few days in deeper soil horizons (Rampazzo et al, 2013) which is similar to Yang et al (2015) and our results (Tables 2 and 3). Glyphosate and AMPA content then correspondingly decreased significantly in deeper soil layers (2-10 cm) and were even below the limit of detection in some layers.…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradation of glyphosate in soil follows two pathways: the oxidative cleavage of the C-N bond to yield aminomethylphosphonic acid (AMPA) and the breaking of the C-P bond to generate sarcosine (Borggaard and Gimsing, 2008). The efficiency of biodegradation can be enhanced by providing suitable conditions for the reproduction of introduced microorganisms (Shushkova et al, 2010). The factors that determine the occurrence and degree of decay of glyphosate in the environment, however, remain to be clarified (Borggaard and Gimsing, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of insecticides in agriculture has been incriminated in the emergence of insecticide in insect vectors (Akogbéto et al, 2005). Glyphosate can bind to soil particles under certain conditions (Shushkova et al, 2009), especially in clay soils. It can be quickly leached in sandy soil, while it may persist for over a year in soils which contain clay (Bergström et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most active glyphosate-degrading microorganisms were isolated from soils polluted by organophosphonates (Shushkova et al, 2010). In soil, glyphosate is primarily decomposed by bacteria and fungi, which utilize glyphosate as carbon source, leading to the production of aminomethylphosphonic acid, or as a phosphorus source, producing glycine (Solomon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%